Master's Degree studies at Rhodes University : access and postgraduate readiness - Stephenson, Sandra Lisa (Rhodes University, Faculty of Education, Department of Education, 2014)
This mixed method, grounded theory study aimed to explore access to Master's level study at Rhodes University, a small, traditional South African university established in 1904, over the ten year period 1999-2008. It also sought to capture the essence of 'postgraduate readiness': the generic (non-certificated) attributes which academics expect graduates to possess in order to undertake Master's degree study. While the majority of students enter Master's level via the formal route (which at Rhodes is an Honours or 4-year bachelor's degree), a significant number are admitted based on the recognition of prior learning (RPL), a practice which is encouraged in South African higher education national policy as a means of widening access and also of acknowledging that learning can take place in ways other than 'formally'. The findings show that while RPL is well defined nationally at the undergraduate level, the concept of RPL at the postgraduate level is vague and largely left to institutional discretion. No national, and few institutional, guidelines are available on which to base the assessment of potential Master's degree students who do not have Honours degrees. Interviews with Deans, supervisors and policy makers at Rhodes indicated that while there is institutional support for admitting alternative access candidates, there is a general perception of deficit compared to those entering the Master's with formal qualifications. However, the statistical findings showed no significant difference in success rates or time taken to completion between students with and without Honours degrees. In addition, comments from supervisors with extensive experience of alternative access students praised the diversity and rich life experience which such students brought to their studies and their peers. The study concludes that an institutional culture characterized by resistance to change, risk and externally imposed regulations at Rhodes has resulted in weak implementation of the University's RPL policy, little marketing or publicizing of alternative access routes to postgraduate study, and low numbers of RPL enrolments at the Master's level. A framework for the assessment of potential Master's candidates - both RPL and formal admissions - for use at Rhodes University and potentially also at other higher education institutions, is proposed in conclusion.
Keywords: Rhodes University; Universities and colleges -- Graduate work; Recognition of prior learning; Graduate students; Corporate culture